The Canadian Concept of Social Security - Martin, Paul (Relations industrielles / Industrial Relations, 1952)
SummaryThe author, instead of concentrating on the crystallization into legislation of the Canadian concept of social security, analyzes the present pattern of social measures administered on the local, provincial and federal levels; he studies the principles on which the programmes are based and to which they must conform. In order to establish such programmes it is necessary to take into account historical factors, deep-seated religious convictions, the experience of older societies and geographic and cultural patterns. To the State belongs the responsibility of helping individuals to provide more adequately for their security and welfare; the State must not be omnipotent and destroy all private or collective initiative in this direction. On each level of government, the Canadian public administrations contribute in a vital way to social welfare.